Examination of Urban Consumers’ Propensity to Consume Margarine by Applying Correspondence Analysis - Nicin, Slobodan (Asian Journal of Agriculture and Rural Development, 2014)
It is well known that margarine as food is of great nutritious significance to the nourishment of the population. The aim of this paper is to carry out research, which is based on the data obtained from the survey, regarding the propensity of urban population market consumers to consume margarine. The survey has been carried out on a representative sample of the citizens of urban area. Correspondence analysis will be used in this paper, with the aim of determining the impact of selected factors on consumers’ preferences for margarine.